Esophageal adenocarcinoma five years after laparoscopic sleeve gastrectomy. A case report. (2017) - Wright, Fernando Gabriel; Duro, Agustin; Medici, Juan Rodolfo; Lenzi, Santiago; Beskow, Axel Federico; Cavadas, Demetrio
Highlights: There is big concern about reflux appearance after sleeve gastrectomy. Chronic reflux increases risk of esophageal adenocarcinoma. We present a case of an esophageal adenocarcinoma after sleeve gastrectomy. Relationship between sleeve gastrectomy and reflux needs further study. Abstract: Introduction: Laparoscopic sleeve gastrectomy has become the most popular bariatric procedure worldwide. However, postoperative gastroesophageal reflux disease appearance is a matter of concern. Only two cases of esophageal adenocarcinoma after gastric sleeve have been described, none of them with preoperative endoscopic evaluation. Presentation of case: We report a case of a 48-year-old male with morbid obesity and normal preoperative endoscopy and esophagram who underwent a laparoscopic sleeve gastrectomy and developed an esophageal adenocarcinoma five years later. Discussion: Despite promising results in terms of weight loss and resolution of comorbidities, the onset or worsening of gastroesophageal reflux and its related complications, such as Barrett's esophagus or esophageal adenocarcinoma, is a matter of concern and need further study. Conclusion: We present a case of an esophageal adenocarcinoma five years after a laparoscopic sleeve gastrectomy for morbid obesity. There is need to better determine the relationship between sleeve gastrectomy and gastroesophageal reflux disease in order to prevent its related complications, such as esophageal adenocarcinoma.